2004
DOI: 10.1124/jpet.104.076711
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitors of Poly(ADP-Ribose) Polymerase Modulate Signal Transduction Pathways and Secondary Damage in Experimental Spinal Cord Trauma

Abstract: Poly(ADP-ribose) polymerase (PARP), a nuclear enzyme activated by strand breaks in DNA, plays an important role in the tissue injury associated with stroke and neurotrauma. The aim of our study was to evaluate the therapeutic efficacy of in vivo inhibition of PARP in an experimental model of spinal cord trauma, which was induced by the application of vascular clips (force of 24g) to the dura via a four-level T5-T8 laminectomy. Spinal cord injury in mice resulted in severe trauma characterized by edema, neutrop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
45
1

Year Published

2005
2005
2014
2014

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 63 publications
(50 citation statements)
references
References 42 publications
4
45
1
Order By: Relevance
“…In this report, an intense immunostaining of nitrotyrosine formation also suggested that a structural alteration of joint had occurred, most probably due to the formation of highly reactive nitrogen derivatives ROS produce strand breaks in DNA, which triggers energy-consuming DNA repair mechanisms and activates the nuclear enzyme poly(ADP-ribosyl) polymerase (PARP). There is various evidence that the activation of PARP may also play an important role in inflammation (Genovese et al, 2005). Continuous or excessive activation of PARP produces extended chains of ADP-ribose (PAR) on nuclear proteins and results in a substantial depletion of intracellular NAD and subsequently, ATP, leading to cellular dysfunction and, ultimately, cell death (Chiarugi, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…In this report, an intense immunostaining of nitrotyrosine formation also suggested that a structural alteration of joint had occurred, most probably due to the formation of highly reactive nitrogen derivatives ROS produce strand breaks in DNA, which triggers energy-consuming DNA repair mechanisms and activates the nuclear enzyme poly(ADP-ribosyl) polymerase (PARP). There is various evidence that the activation of PARP may also play an important role in inflammation (Genovese et al, 2005). Continuous or excessive activation of PARP produces extended chains of ADP-ribose (PAR) on nuclear proteins and results in a substantial depletion of intracellular NAD and subsequently, ATP, leading to cellular dysfunction and, ultimately, cell death (Chiarugi, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…For example, in a spinal cord trauma model, the infiltration of neutrophils in spinal cord tissue was associated with a marked increase in immunoreactivity for PARs, an index of PARP activation; and treatment with PARP-1 inhibitors reduced the tissue inflammation and injury events associated with spinal cord trauma. 50 In another study, 51 PARP-1-deficient or wild-type mice treated with PARP-1 inhibitors [PJ34 (N-[6-oxo-5,6-dihydro-phenanthridin-2-yl]-N,N-dimethylactamide) or 3AB (3-aminobenzaminde)] were subjected to heat exposure as a model to study heat stroke. The PARP-1 inhibition increased the expression of 27-and 70-kDA heat shock proteins, and heat stroke-induced liver injury was attenuated in PARP-1-deficient mice when compared with findings in wild-type mice.…”
Section: Involvement Of Parp-1 In Inflammatory Diseasesmentioning
confidence: 99%
“…Excessive activation of PARP in response to extensive DNA damage has been associated with the depletion of NAD + , which causes cell death through energy depletion (22). It was recently reported that ONOO --induced toxicity in spinal cord neurons is associated with DNA strand breakage and prevented by PARP inhibition (23).…”
Section: Introductionmentioning
confidence: 99%